Chronic Hexavalent Chromium Exposure Upregulates the RNA Methyltransferase METTL3 Expression to Promote Cell Transformation, Cancer Stem Cell-Like Property, and Tumorigenesis. (24th February 2022) - Wang, Zhishan; Uddin, Mohammad Burhan; Xie, Jie; Tao, Hua; Zeidler-Erdely, Patti C; Kondo, Kazuya; Yang, Chengfeng
Abstract: Hexavalent chromium [Cr(VI)] is a common environmental carcinogen causing lung cancer in humans. This study investigates the mechanism of Cr(VI) carcinogenesis focusing on the role of the epitranscriptomic dysregulation. The epitranscriptomic effect of Cr(VI) was determined in Cr(VI)-transformed human bronchial epithelial cells, chromate-exposed mouse and human lungs. The epitranscriptomic effect and its role in Cr(VI)-induced cell transformation, cancer stem cell (CSC)-like property, and tumorigenesis were determined by microarray analysis, soft agar colony formation, suspension spheroid formation, and mouse xenograft tumorigenesis assays. It was found that chronic Cr(VI) exposure causes epitranscriptomic dysregulations as evidenced by the increased levels of total RNA N 6 -methyladenosine (m 6 A) modification and the RNA m 6 A methyltransferase like-3 (METTL3) in Cr(VI)-transformed cells and chromate exposure-caused mouse and human lung tumors. Knockdown of METTL3 expression in Cr(VI)-transformed cells significantly reduces their m 6 A levels and transformed phenotypes and tumorigenicity in mice. Moreover, knockdown of METTL3 expression in parental nontransformed cells significantly reduces the capability of chronic Cr(VI) exposure to induce cell transformation and CSC-like property. Together, this study reveals that chronic Cr(VI) exposure is capable of altering cellular epitranscriptome by increasing the m 6 A RNA modification via upregulating the RNA methyltransferase METTL3 expression, which plays an important role in Cr(VI)-induced cell transformation, CSC-like property, and tumorigenesis.